Cassane diterpenoids from the roots of Caesalpinia decapetala var. japonica and structure revision of caesaljapin. (January 2016) - Kamikawa, Sayuri; Oshimo, Shiori; Ohta, Emi; Nehira, Tatsuo; Ômura, Hisashi; Ohta, Shinji
Graphical abstract: Three diterpenoids (1 –3 ) were isolated from the roots of Caesalpinia decapetala var. japonica and the structures were determined based on spectroscopic data as well as X-ray diffraction analysis. Furthermore, the originally proposed structure4′ for caesaljapin was revised to4 . Highlights: Cassane-type furanoditerpenoids were isolated from the roots of Caesalpinia decapetala var. japonica . Their structures were elucidated by 2D NMR and X-ray analysis. Their absolute configurations were determined via TDDFT calculations of the ECD spectra. Previously reported structure of caesaljapin was revised as its C-4 epimer by X-ray analysis. Abstract: Two cassane-type furanoditerpenoids, designated caesalacetal and caesalpinetate, and a norditerpenoid designated caesalpinone were isolated from the roots of Caesalpinia decapetala var. japonica along with seven known diterpenoids. Structures were elucidated by interpretation of their spectroscopic data, and the absolute structure of caesalacetal was confirmed by X-ray crystallographic analysis. Furthermore, the structure of a previously reported furanoditerpenoid, caesaljapin, was revised as its C-4 epimer on the basis of detailed NMR spectroscopic data as well as X-ray crystallographic analysis.